PEMBERDAYAAN PETANI KOPI OLEH DINAS PERTANIAN DI DESA RAMUNG JAYA KECAMATAN PERMATA KABUPATEN BENER MERIAH PROVINSI ACEH - Kasihan Hati Kasmita; Eva Eviany; Achmad Nur Sutikno (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2021)
Empowerment of farmers is an activity that involves the participation and leadership of farmer groups. This empowerment is shown to improve the quality and creativity of farmers to create reliable and independent farmers who can have innovations for their own farmers. This research intend to knowing and analyzing how community empowerment of coffe farmers at Ramung Jaya Village by the department of agricultural Bener Meriah Regency as well as to determine the inhibiting factors and the efforts made in empowering coffee farmers by the Bener Meriah Regency Agriculture Office in Ramung Jaya Village.The method used in this research is descriptive qualitative research method. Data collection techniques used were observation, interviews, and documentation. In addition, to analyze data using several steps, namely data reduction, data presentation, and drawing conclusions and verification Based on the results of the study, it shows that the implementation of empowerment carried out by the Agriculture Office of Bener Meriah Regency for coffee farmers in Ramung Jaya Village has been going well, but there are still several obstacles for both the government and coffee farmers in Ramung Jaya Village. The author also provides suggestions or recommendations to the government in order to increase creativity and quality through counseling to improve the quality of farmers and pay more attention to the provision of facilities and infrastructure and can provide business capital assistance. Keywords: Empowerment, Economic Development, Coffee Farmers.